Further Evidence that Glycoprotein IIb-IIIa Mediates Platelet Spreading on Subendothelium - Weiss, Harvey J; Turitto, Vincet T; Baumgartner, Hans R (Thrombosis and Haemostasis, 1991)
In order to explore further the mechanism by which glycoprotein GPIIb-IIIa promotes platelet vessel wall interaction, platelet adhesion to subendothelium was studied in an annular chamber in which subendothelium from rabbit aorta was exposed at a shear rate of 2,600 s−1 to blood from patients with thrombasthenia. Perfusions were conducted for each of 5 exposure times (1 ,2,3, 5 and 10 min), and the percent surface coverage of the vessel segment with platelets in the contact (C) and spread (S) stage was determined. Increased values of platelet contact (C) were obtained in thrombasthenia at all exposure times; this finding is consistent with a defect in platelet spreadirg, based on a previously described kinetic model of platelet attachment to subendothelium. According to this model of attachment, increased values of platelet contact (C) at a single exposure time may be indicative of either a defect in spreading (S) or initial contact (C), but multiple exposures will result in increased contact only for defects which are related to defectiye platelet spreading (s).The results obtained over a broad range of exposure times provide more conclusive evidence that GPIIb-IIIa mediates platelet spreading than those previously obtained at single exposure times.